Finnish nationwide controlled register study found increased inpatient infections in children with 22q11.2 deletion syndrome - Wahrmann, Sakari; Kainulainen, Leena; Lempainen, Johanna; Kytö, Ville (WILEY, 2025)
Aim
Studies on treating infections in children with 22q11.2 deletion syndrome (22q11.2DS) have been limited. We characterised inpatient infections and outpatient antibiotic treatment.
Methods
Children born during 2005–2018 were eligible for this national Finnish retrospective register-based study. We recruited 98 children (54% male) with DiGeorge or velocardiofacial syndrome. The 980 matched controls had a benign murmur diagnosed before 1 year of age. The cumulative incidence of infections and antibiotic prescriptions and total prescriptions were measured.
Results
The median age for 22q11.2DS diagnoses was under 1 year of age (range 0–14 years), with a median follow-up time of 9 years for diagnoses and 11 years for prescriptions. Children with 22q11.2DS had significantly higher hospitalisation rates than the controls for any infection (68.1% vs. 30.5%), gastroenteritis (16.8% vs. 4.0%), pneumonia (23.4% vs. 4.3%), severe bacterial infections, excluding pneumonia or pyelonephritis (15.0% vs. 4.1%) and viral wheezing (23.2% vs. 9.1%). Outpatient antibiotic prescriptions were similar, but the children with 22q11.2DS received them earlier than the controls, with a hazard ratio of 3.29 for ages 0–5 years and 1.84 for the entire follow-up.
Conclusion
Children with 22q11.2DS had significantly more infections requiring hospitalisation than controls without the syndrome.